2019
DOI: 10.3390/foods9010027
|View full text |Cite
|
Sign up to set email alerts
|

Recombinase Polymerase Amplification (RPA) Combined with Lateral Flow Immunoassay for Rapid Detection of Salmonella in Food

Abstract: Salmonella can cause serious foodborne diseases. We have developed a lateral flow immunoassay combined with recombinase polymerase amplification (LFD-RPA) for detection of Salmonella in food. The conserved fragment (fimY) was selected as the target gene. Under an optimal condition (37 °C, 10 min), the sensitivity was 12 colony-forming units (CFU)/mL in a pure culture. Testing with 16 non-Salmonella strains as controls revealed that LFD-RPA was specific to the fimY gene of Salmonella. The established assay coul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
43
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(47 citation statements)
references
References 30 publications
4
43
0
Order By: Relevance
“…causes food poisoning, typhoid fever, gastrointestinal inflammation, and septicemia for both humans and animals ( McGuinness et al, 2009 ; Rukambile et al, 2019 ). Currently, there are over 80 million cases of foodborne salmonellosis in the world ( Li et al, 2019 ). Additionally, reports revealed that outbreaks caused by Salmonella spp.…”
Section: Introductionmentioning
confidence: 99%
“…causes food poisoning, typhoid fever, gastrointestinal inflammation, and septicemia for both humans and animals ( McGuinness et al, 2009 ; Rukambile et al, 2019 ). Currently, there are over 80 million cases of foodborne salmonellosis in the world ( Li et al, 2019 ). Additionally, reports revealed that outbreaks caused by Salmonella spp.…”
Section: Introductionmentioning
confidence: 99%
“…The exponential amplification can be detected within 30 min in a temperature range of 37 to 42 °C [ 19 ]. Recently, several applications of RPA in DNA and RNA target detection have been proved [ 20 , 21 ], and the integration of RPA in different platforms has been reported [ 22 , 23 , 24 ]. Lateral flow dipsticks (LFD) has great application prospects in the detection field due to easy-to-use, high sensitivity, less time consuming and low-cost [ 25 , 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…But, designing of RPA probe and primers are still difficult, as several sets of primers must be checked for the selection of a working set, as there is no suitable available software so far. RPA has several important advantages over PCR methods, the first being that it does not require a pure template for the analysis, which is required for PCR-based assays ( Mekuria et al., 2014 ; Li et al., 2019 ). The second advantage is that results are available in a much shorter time i.e., 15–20 min for RPA and 1.5-3.0 h for PCR assays.…”
Section: Discussionmentioning
confidence: 99%